Lysosomal P-gp-MDR1 Confers Drug Resistance of Brentuximab Vedotin and Its Cytotoxic Payload Monomethyl Auristatin E in Tumor Cells - Liu-Kreyche, Peggy; Shen, Hong; Marino, Anthony M.; Iyer, Ramaswamy A.; Humphreys, W. Griffith; Lai, Yurong (Frontiers in Pharmacology, 2019)
Antibody-drug conjugates (ADCs) are composed of an antibody linked to cytotoxic anticancer payloads. ADCs recognize tumor-specific cell surface antigens and are internalized into lysosomes where proteolytic enzymes release the cytotoxic payloads. Efflux transporters on plasma membrane that play a significant role on multi-drug resistance in chemotherapy, can be internalized on lysosomal membrane and sequester the cytotoxic payloads. In the present study, ATP binding cassette (ABC) efflux transporters including breast cancer resistance protein (BCRP), P-glycoprotein (P-gp-MDR1), multidrug resistance protein (MRP) 2, MRP3 and MRP4 in lysosomal and plasma membrane of tumor cells were quantified by targeted quantitative proteomics. The cytotoxicity of brentuximab vedotin and its cytotoxic payload monomethyl auristatin E (MMAE) to the tumor cell lines in the presence and absence of elacridar (P-gp-MDR1 inhibitor) or chloroquine (lysosomotropic agent) were evaluated. MMAE is a substrate for P-gp-MDR1, as the apparent efflux ratio in MDR1 transfected MDCK cell monolayers was 44.5, and elacridar abolished the MMAE efflux. Cell lines that highly express P-gp-MDR1 show higher EC50s towards the cell killing effects of MMAE. Co-incubation with chloroquine or elacridar resulted in left-shift of MMAE EC50 by 2.9 16 fold and 4.2 to 22 fold, respectively. Similarly co-incubation with chloroquine or elacridar or in combination of chloroquine and elacridar increased cytotoxic effects of brentuximab vedotin by 2.8 to 21.4-fold on KM-H2 cells that express a specific tumor antigen CD30 and P-gp-MDR1. These findings demonstrate important roles of P-gp-MDR1 on cytotoxic effects of brentuximab vedotin and its payload MMAE. Collectively, ABC transporter-mediated drug extrusion and/or sequestration needs to be early assessed for selection of optimal payloads and linkers when developing ADCs.